Administrative means of protecting the environment from pollution caused by the exploitation of industrial real estate in Algerian Law - Imene, Abbane (The International tax journal, 2026)
In the early 1970s, the world witnessed an increase in environmental awareness, which led to a commitment to the implementation of environmental policies. However, the exploitation of industrial drugs led to serious environmental problems, despite efforts to protect the ecosystem. Industrial pollution was circumvented as a result of the misuse of industrial drugs, making life on the planet almost impossible.